2005
DOI: 10.1017/s1355770x0400186x
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity and nature-based tourism at forest reserves in Uganda

Abstract: The benefits of nature-based tourism to biodiversity conservation are often presumed but rarely quantified. The relative value placed on attributes of nature parks is unknown, as is the contribution of biodiversity to tourists' willingness to visit a particular protected area. We surveyed tourists and foreign residents in Uganda to determine how preferences for particular protected areas are formed. We evaluated tourists' demand for elevated biodiversity levels (increased numbers of bird species seen), relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
88
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(96 citation statements)
references
References 43 publications
3
88
0
1
Order By: Relevance
“…For example, this technique was employed to examine tourists' preferences associated with ecotourism development [11,12], tourists' preferences for biodiversity conservation and scenic beauty [13], and tourist preferences for ecotourism development in protected areas [14,15]. Furthermore, some other studies used this approach to evaluate the tourists' preferences for effective attributes associated with tourism resources [16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…For example, this technique was employed to examine tourists' preferences associated with ecotourism development [11,12], tourists' preferences for biodiversity conservation and scenic beauty [13], and tourist preferences for ecotourism development in protected areas [14,15]. Furthermore, some other studies used this approach to evaluate the tourists' preferences for effective attributes associated with tourism resources [16][17][18][19][20][21][22].…”
Section: Methodsmentioning
confidence: 99%
“…Of course, most recreation activities depend on built infrastructure, accessibility, and other factors, but the fundamental importance of ecological conditions has been widely demonstrated (76)(77)(78)(79). For a specific example, Fuller et al (77) surveyed visitors to urban/suburban parks and found that psychological well-being (gauged by factors derived from park visitor's reports, including reflection, identity, and attraction) was positively correlated with the species richness and habitat diversity in the park.…”
Section: Scientific Foundations For Integrating Cultural Servicesmentioning
confidence: 99%
“…In support of such assessments, emerging visitor simulation models can determine the effects of changes in environmental characteristics on visitor behavior in space and time (81)(82)(83)(84), information that is also essential for assessments of impacts of use on affected ecosystems. At finer scales, assessments of particular activities at particular sites can be extended to detailed models that quantify the specific contributions of setting characteristics, such as scenic beauty or the probability of wildlife encounters (78,88), fitting the capture tier of the model of TEEB (16). More comprehensive approaches, including qualitative and quantitative research methods, such as in-depth interviews and tape recordings, to capture immediately recalled leisure experiences (89), on-site measurements of hiking experiences via questionnaires (89), and computer-animated choice experiments for recreational trail preferences (90) can further guide and help to justify ecosystem protection policies.…”
Section: Scientific Foundations For Integrating Cultural Servicesmentioning
confidence: 99%
“…T o inform decision makers about how they can best allocate resources to maintain and enhance ecosystem services, scholars need to develop a better understanding of how policy interventions actually affect the supply of ecosystem services. In the last two decades, scholars have made important advances in defining, measuring, and valuing ecosystem services across time and space (1)(2)(3)(4)(5)(6)(7). These measures and values have in turn been used as conservation planning and resource management decision tools (8)(9)(10)(11).…”
mentioning
confidence: 99%